Desarrollo de competencias relacionadas al cuidado de las personas con discapacidad entre estudiantes de las profesiones de la salud: Un estudio piloto - Castro, Shamyr Sulyvan; Rowe, Michael; Andrade, Luana Foroni; Cyrino, Eliana Goldfarb [UNESP] (FapUNIFESP (SciELO), 2018)
This is a two-phase study, the first was a literature review that aimed to identify a set of competencies for professional practice that would be relevant for the health care of People with disabilities (PwD). These competencies were then used to plan a thirty-hour multidisciplinary course for undergraduate health care students. The educational intervention led to improvements in the students’ learning experiences, including the development of empathy and knowledge related to the care of PwD, improved knowledge around accessibility, and an awareness of the need to humanize the care of PwD. Students reported enhanced learning experiences and an increase in knowledge related to the care of PwD, and also highlighted the need to humanize the care.
Desenvolvimento de competências relacionadas ao cuidado das pessoas com deficiência entre estudantes das profissões da saúde: Um estudo piloto
Developing competencies among health professions students related to the care of people with disabilities: A pilot study
Keywords: Disabled persons; Health care; Health education